Percolative silver nanoplates/PVDF nanocomposites: Bulk and surface electrical conduction. (5th November 2015) - Audoit, Jérémie; Laffont, Lydia; Lonjon, Antoine; Dantras, Eric; Lacabanne, Colette
Abstract: Electrically conductive polymer composites have been elaborated by dispersing silver microplates into a polyvinylidene fluoride (PVDF) matrix. Silver microplates have been successfully synthesized. Their mean lateral length is about 1.15 μm, presenting a moderate aspect ratio (12–25). Synthesis is easily controlled and can produce 1–500 mg depending on the volume and the concentration of the solutions used. Electrical bulk and surface conductivity of the composites containing different filler fractions (4–20 vol.%) have been determined for each sample. Electrical percolation has been observed for each situation and was determined at 5.9 vol.% for bulk conductivity (through the thickness), while the value is shifted to 6.9 vol.% when surface conductivity is considered. The gap between the two values of percolation threshold is attributed to the orientation of fillers. Bulk conductivity and surface resistivity reaches 12.9 S m −1 and 0.123 Ω/☐ respectively at filler fraction of 15 vol.%. Graphical abstract: Highlights: Extended lab scale production of Ag microplates obtained by a seeded-growth method. Electrically conductive PVDF/AgMicroplates nanocomposites were elaborated. Electrical bulk percolation threshold: 5.9 vol.%. Electrical surface percolation threshold: 6.9 vol.%.